1995
DOI: 10.1104/pp.109.3.1115
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Partial Characterization of Tomato Extensin Peroxidase

Abstract: Early plant defense response is characterized by elevation of activity of peroxidases and enhanced insolubilization of hydroxyproline-rich glycoproteins, such as extensin, i n the cell wall.The insolubilization process (cross-linking between soluble extensin precursor molecules) is catalyzed by extensin peroxidases. We have ionically eluted extensin peroxidases from intact water-washed suspension-cultured tomato (hybrid of Lycopersicon esculenfum Mill.and Lycopersicon peruvianum L. [Mill.]) cells and purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
43
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 24 publications
5
43
0
1
Order By: Relevance
“…Confirming this, two of the internal peptide sequences obtained from GvEP could be mapped to conserved sequences in helixes B and J of the class III peroxidase structure (Schuller et al, 1996;Gajhede et al, 1997;Mirza et al, 1999). To date, the purification of only three other EPs has been reported (Brownleader et al, 1995;Schnabelrauch et al, 1996;Jackson et al, 1999) and none of these unusual peroxidases have been sequenced. Obtaining further peptide sequences of GvEP leading to the isolation of its cDNA clone therefore would be informative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirming this, two of the internal peptide sequences obtained from GvEP could be mapped to conserved sequences in helixes B and J of the class III peroxidase structure (Schuller et al, 1996;Gajhede et al, 1997;Mirza et al, 1999). To date, the purification of only three other EPs has been reported (Brownleader et al, 1995;Schnabelrauch et al, 1996;Jackson et al, 1999) and none of these unusual peroxidases have been sequenced. Obtaining further peptide sequences of GvEP leading to the isolation of its cDNA clone therefore would be informative.…”
Section: Discussionmentioning
confidence: 99%
“…In the tomato system, at least two peroxidases have been demonstrated to have a high capacity for the oxidative cross-linking of extensin, whereas other tomato peroxidases (Brownleader et al, 1995) and several others derived from different species (Schnabelrauch et al, 1996) did not. A basic peroxidase with a similarly high capacity recently was purified from lupin, whereas an acidic form presented negligible activity against extensin (Jackson et al, 1999).…”
mentioning
confidence: 99%
“…Although the pI 4.6 isozyme has a specific activity 2-3 orders of magnitude greater than a basic tomato peroxidase that crosslinks P1 extensin in vitro (23), its substrate range remains undefined. Conceivably, the cross-linking of multiple extensins might involve multiple extensin peroxidases, as several extensin peroxidases have been identified in a range of species (20,23,24,47). We therefore tested a P3 analog, YK20, as a substrate.…”
Section: Figmentioning
confidence: 99%
“…However, to date we lack direct demonstration of an extensin intermolecular cross-link. The results of extensin in vitro cross-linking assays have been difficult to interpret as the cross-linking substrates contained both Tyr and Lys in more than one type of repetitive motif, and the amino acids formed by cross-linking were not identified (20,23,24). Other approaches involving the isolation of intermolecularly crosslinked peptides from the cell wall itself have also proven intractable.…”
mentioning
confidence: 99%
“…In these myc-mutants fungal strains of Glomus mosseae, which successfully formed arbuscular mycorrhizae on wild-type pea, failed to differentiate mycorrhizal structures because of the induction of physical barriers in the plant tissue located under the appressoria . It is known that elicitors can trigger processes such as lignification, callose apposition, and peroxidative crosslinking of extensin, which are the basis for an induced barrier formation in plant cell walls (Benhamou and Lafontaine, 1995;Brownleader et al, 1995). In this respect it was shown that elicitors released by the ectomycorrhizal fungus Hebeloma crustuliniforme (Bull.…”
mentioning
confidence: 99%